Production of sophorolipids by Starmerella bombicola yeast using new hydrophobic substrates - Shah, M.U.H. (Elsevier B.V., 2017)
Sophorolipids (SLs) are surface active compounds that have excellent surface-lowering properties. Typically, SLs are produced using different hydrophobic substrates, such as alkanes, vegetable oils, and industrial effluents. The properties of the SLs are highly dependent on the hydrophobic substrate used for their production. The aim of the present study is to investigate the properties of SLs produced using three new hydrophobic substrates: Tapis oil, Melita oil, and Ratawi oil. The structures of the SLs were determined by Fourier transform infrared spectroscopy. The SLs yields using Tapis, Melita, and Ratawi oil were 26, 21, and 19 g L−1, respectively. The SLs produced using Tapis, Melita, and Ratawi oil reduced the surface tension of pure water to 36.38, 37.84, and 38.92 mN/m, respectively, corresponding to critical micelle concentrations (CMCs) of 54.39, 55.68, and 58.34 mg L−1. These values are comparable with SLs produced using palm oil (surface tension 35.38 mN/m and CMC 48.76 mg L−1). The SLs produced using Tapis oil show a maximum emulsification activity of 71.2. The produced SLs are active over the pH range 2–10 and for salinity up to 20 (w/v) NaCl. Thus, they show potential for various applications, including microbial enhanced oil recovery and oil spill remediation. © 2017 Elsevier B.V.